The HHIP-AS1 lncRNA promotes tumorigenicity through stabilization of dynein complex 1 in human SHH-driven tumors - Bartl, Jasmin; Zanini, Marco; Bernardi, Flavia; Forget, Antoine; Blümel, Lena; Talbot, Julie; Picard, Daniel; Qin, Nan; Cancila, Gabriele; Gao, Qingsong; Nath, Soumav; Koumba, Idriss Mahoungou; et al. (Nature Communications, 2022)
Most lncRNAs display species-specific expression patterns suggesting that animal models of cancer may only incompletely recapitulate the regulatory crosstalk between lncRNAs and oncogenic pathways in humans. Among these pathways, Sonic Hedgehog (SHH) signaling is aberrantly activated in several human cancer entities. We unravel that aberrant expression of the primate-specific lncRNA HedgeHog Interacting Protein-AntiSense 1 (HHIP-AS1) is a hallmark of SHH-driven tumors including medulloblastoma and atypical teratoid/rhabdoid tumors. HHIP-AS1 is actively transcribed from a bidirectional promoter shared with SHH regulator HHIP. Knockdown of HHIP-AS1 induces mitotic spindle deregulation impairing tumorigenicity in vitro and in vivo. Mechanistically, HHIP-AS1 binds directly to the mRNA of cytoplasmic dynein 1 intermediate chain 2 (DYNC1I2) and attenuates its degradation by hsa-miR-425-5p. We uncover that neither HHIP-AS1 nor the corresponding regulatory element in DYNC1I2 are evolutionary conserved in mice. Taken together, we discover an lncRNA-mediated mechanism that enables the pro-mitotic effects of SHH pathway activation in human tumors.